Garlic (Allium sativum L.): A review of varied health benefits - Natalia Aleksandra Popławska; Justyna Śliz; Marta Skorupska; Magdalena Joanna Czeczotka; Krzysztof Woźniak (Kazimierz Wielki University, 2024)
Introduction:   Garlic (Allium sativum L.), has been cultivated in various countries and is valued for its medicinal and culinary properties. It contains bioactive compounds such as phenolic compounds, organic sulfides, polysaccharides, and saponins, with allicin being a particularly studied compound. These compounds have been shown to possess antioxidant, antimicrobial, antiviral, anticancer, anti-inflammatory, anti-hyperlipidemic and antihypertensive effects. Garlic has been used for over 5000 years as a curative plant and has potential applications in food science, medicine, and nutraceuticals.  Aim of the Study:   The aim of the study is to provide a comprehensive review of the overall impact of Allium sativum L. on human health and in order to draw attention to the benefits of regular consumption.  Materials and methods:  A comprehensive review of scientific and medical literature was conducted utilizing PubMed and Google Scholar databases. Searching terms were: garlic, Allium sativum L., garlic anti-inflammatory, garlic anticancer, garlic health effects.   Conclusion:   Allium sativum L. is associated with a comprehensive range of beneficial effects on the human body. These include anti-inflammatory and antioxidant properties, positive influence on lipid profile, cardiovascular system, and the anticancer activity among others by stimulation of tumor apoptosis. As a result, garlic and its bioactive compounds hold promise as functional foods or nutraceuticals for the prevention and treatment of various diseases.